2021
DOI: 10.14744/ejmo.2021.16263
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Ivermectin-Doxycycline and Hydroxychloroquine-Azithromycin Therapy on COVID-19 Patients

Abstract: Background The worldwide COVID-19 pandemic was caused by a newly discovered Coronavirus. The treatment methods for COVID-19 are emerging and rapidly evolving. Existing drugs, including Ivermectin and Hydroxychloroquine, offer the hope of effective treatment in early disease. In this study, we investigated and compared outcomes of Ivermectin-Doxycycline vs. Hydroxychloroquine-Azithromycin combination therapy COVID19 patients with mild to moderate disease.Methods Patients with mild to moderate COVID-19 disease, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…IRB approval was exempted because data was extracted from publicly available studies. We also analyzed raw data files or supplemental files of studies by Cadegiani 42 and Lima-Morales et al 43 for outcomes of cases receiving Ivermectin, Niaee et al 44 for clinical severity based mortality data and duration of hospital stay, Choudhary et al 35 for time for viral clearance, Mahmud et al 45 for need for hospitalization, Ghooi et al 46 for mortality in Ivermectin receiving patients, Samaha et al 47 for viral clearance. In Cadegiani et al’s study 42 , we considered ‘CG1’ as control group because only this sample was demographically comparable to the treatment group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IRB approval was exempted because data was extracted from publicly available studies. We also analyzed raw data files or supplemental files of studies by Cadegiani 42 and Lima-Morales et al 43 for outcomes of cases receiving Ivermectin, Niaee et al 44 for clinical severity based mortality data and duration of hospital stay, Choudhary et al 35 for time for viral clearance, Mahmud et al 45 for need for hospitalization, Ghooi et al 46 for mortality in Ivermectin receiving patients, Samaha et al 47 for viral clearance. In Cadegiani et al’s study 42 , we considered ‘CG1’ as control group because only this sample was demographically comparable to the treatment group.…”
Section: Methodsmentioning
confidence: 99%
“…An Australian study demonstrated the effectiveness of Ivermectin in inhibiting SARS-COV2 in-vitro 31 . Subsequently, several Ivermectin-based clinical trials and observational studies conducted globally showed mostly positive results 32-35 . Some countries have incorporated this therapy in their COVID-19 guidelines 36-39 .…”
Section: Introductionmentioning
confidence: 99%
“…It's the exact opposite of what normally happens, where doctors are telling the patients" (Sy 2021). Just as graduate students may be more familiar with contemporary scholarship than their overworked advisors, bed-bound patients may oft en be more versed in PubMed research or new clinicals than harried clinicians about the potential off -label prescription of ivermectin to treat COVID-19 (Chowdhury 2020).…”
Section: Vulnerability In a Time Of Covidmentioning
confidence: 99%
“…With their pleiotropic features, including anti-inflammatory and antioxidant properties, and their ability to chelate zinc compounds on matrix metalloproteinases [ 4 ], tetracyclines have been proposed, alone or combined with other compounds, as potential therapeutic candidates against COVID-19 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Second-generation tetracyclines, such as minocycline and doxycycline, exerted a direct antiviral effect and can inhibit the replication of different viruses, including the human immunodeficiency virus (HIV), West Nile virus, Japanese encephalitis virus, and influenza virus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tetracyclines, alone or together with colchicine, have therefore been given to COVID-19 patients in a non-hospital setting and have been reported to improve symptoms and hasten recovery in case reports [ 18 ] and observational clinical studies [ 19 , 20 ]. Doxycycline combined with Ivermectin has recently resulted in better symptomatic relief, shortened recovery duration, fewer adverse effects, and superior patient compliance compared to the Hydroxychloroquine-Azithromycin combination in patients with mild to moderate COVID-19 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%